2016
DOI: 10.1007/s00423-016-1513-1
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative oral antibiotics reduce infections after colorectal cancer surgery

Abstract: AimThe objectives were to recognize the risk factors for surgical site infections (SSIs) after surgery due to colorectal cancer and to assess the impact of mechanical bowel preparation (MBP) and oral antibiotic prophylaxis (ABX) on SSIs.MethodsRecords from two colorectal centers were used. Risk factors of SSIs were categorized into patient-, disease-, and treatment-dependent.ResultsA group of 2240 patients was included. SSIs were noted in 364 patients (16.3 %). MBP+/ABX+ was connected with a lower incidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 31 publications
0
36
0
Order By: Relevance
“…From the 520 studies identified in the initial search, 40 studies 31 , 41 , 43 , 45 , 46 , 49 83 on 69,517 participants were included ( Supplementary Figure 1 , http://links.lww.com/SLA/B542 ). Of these 28 were RCTs with 6437 participants 49 53 , 55 59 , 61 67 , 69 – 73 , 75 , 76 , 78 80 , 83 and 12 were cohort (case control) studies with 63,080 participants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From the 520 studies identified in the initial search, 40 studies 31 , 41 , 43 , 45 , 46 , 49 83 on 69,517 participants were included ( Supplementary Figure 1 , http://links.lww.com/SLA/B542 ). Of these 28 were RCTs with 6437 participants 49 53 , 55 59 , 61 67 , 69 – 73 , 75 , 76 , 78 80 , 83 and 12 were cohort (case control) studies with 63,080 participants.…”
Section: Resultsmentioning
confidence: 99%
“…Of these 28 were RCTs with 6437 participants 49 53 , 55 59 , 61 67 , 69 – 73 , 75 , 76 , 78 80 , 83 and 12 were cohort (case control) studies with 63,080 participants. 31 , 41 , 43 , 45 , 46 , 54 , 60 , 68 , 74 , 77 , 81 , 82 The risk of bias in the RCTs included was variable, with poor levels of documentation particularly surrounding randomization methods, allocation concealment, and blinding in the earlier studies ( Table 1 ). Six studies 57 , 58 , 62 , 64 – 66 administered different parenteral antibiotic regimens depending upon whether the patient was receiving MBP+OAB or MBP alone, which may provide significant source of bias in terms of SSI prevention.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the gut is constantly exposed to a high burden of microbial organisms, healing may be dependent on a delicate balance between the health‐promoting microbiota and the virulence of pathobiota. Studies in animals as early as 1955 demonstrated a key role for the colonic microbiota in the pathogenesis of anastomotic healing. A more recent study examining anastomotic tissues in rodents showed a significant loss of health‐promoting taxa such as Ruminococcus , Bacteroidales family S24‐7 and Prevotellaceae , with a significant bloom in Escherichia and Enterococcus .…”
Section: Introductionmentioning
confidence: 99%